Between knowledge and risk: The reality of self-medication among health science undergraduate students (Research, Society and Development, 2025)
Introduction: Self-medication is a highly prevalent practice in Brazil. However, when carriedout improperly, it can become a serious problem, leading to undesirable consequences.Objective: To assess the risks associated with self-medication among undergraduate Dentistrystudents at Parana University (UNIPAR), in Cascavel, Paraná.Methods: This cross-sectional, original study employed a digital questionnaire addressing theuse of medications without medical prescription among students enrolled in health-relatedcourses at UNIPAR.Results: A total of 303 students participated, 77.22% of whom were female, with the majoritybetween 18 and 24 years old (80.85%). Among them, 51.72% reported frequentself-medication and 41.37% occasional use, totaling over 90% of respondents, in line withfindings from other studies. The most common symptom prompting self-medication washeadache, and the most frequently used drugs included analgesics, antipyretics, andanti-inflammatory agents, due to ease of access. The main influencing factors were advicefrom friends, neighbors, and relatives (84.15%), as well as media advertising (37.62%). Although 63.69% of participants reportedbeing aware of the risks, 22.44% experienced adverse reactions, most frequently headache(15%) and drowsiness (19.14%). The main sources of information were family members andpharmacists.Conclusion: The findings reinforce that, despite its frequency, self-medication posessignificant risks, including drug resistance, harmful interactions, and worsening of clinicalconditions. These results highlight the urgent need for educational campaigns and stricterregulatory measures to reduce this practice.